Pengaruh Akuntabilitas Publik dan Pemanfaatan Aplikasi Sistem Keuangan Desa Terhadap Kinerja Manajerial Perangkat Desa dengan Moderasi Sistem Pengendalian Internal - Aditya Cindy Faticha; Sri Anik (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to analyze the influence of public accountability, the use of village financial system applications on the managerial performance of village apparatus with the moderation of the internal control system. This type of research is quantitative research. The population in this study is a village apparatus located in the Karanganyar sub-district, Demak. And the samples are the village head, the chairman of the village consultative body, and the treasurer. With the sampling technique used in this study, multiple linear regression analysis with interactive tests (MRA) is used to analyze public accountability variables, the use of village financial system applications as independent variables for the managerial performance of village apparatus as a dependent variable with internal control systems as a moderation variable. The data obtained will be processed and analyzed with SPSS 29.0. The results in this study are as follows: Public accountability has a positive and significant effect on the managerial performance of village apparatus. The use of village financial system applications has a positive and significant effect on the managerial performance of village apparatus. Internal control has been proven to be able to moderate public accountability and the use of village financial system applications on the influence of the managerial performance of village apparatus.